Is It Worth Publishing in a Medical Students' Journal? Insights From a 10-Year Journey - Francisco J. Bonilla-Escobar; Ciara Egan; Mihnea-Alexandru Găman (University Library System, University of Pittsburgh, 2022)
Very little has been said about young scientists publishing in Journals that are led and carried forward by medical students or recently graduated physicians themselves. What has been said, however, is not always supportive. For some, these Journals should not exist, arguing that medical student research is for the sole purpose of training or rather, it should be aimed at reaching the level of rigor and impact held by other professional journals. For others, the lack of indexing and impact make these Journals a place where potential visibility and recognition is lost. Yet, there is a community of believers who see us as a way to improve science by training the next generation from the onset of their careers. A for-students, by-students Journal is the crossroads between publication, and therefore visibility, of student research, and a training ground for the ins and outs of peer-review and the writing standards held in science and medicine. With time, the rigor and excellence of these journals grows, and indexing follows. We shared exciting news as well as a summary of the articles that we are publishing in this issue.